Effect of partial substitution of corn straw fly ash for fly ash as supplementary cementitious material on the mechanical properties of cemented coal gangue backfill. (19th April 2021) - Wang, Haochen; Qi, Tingye; Feng, Guorui; Wen, Xiaoze; Wang, Zehua; Shi, Xudong; Du, Xianjie
Highlights: Up to 40 wt% of fly ash can be replaced with corn straw fly ash. Corn straw fly ash has a coarser particle size and higher pozzolanic reactivity. As substitution amount increased, failure form gradually changed to X-shaped. The introduction of corn straw fly ash improves mechanical properties. Abstract: Cemented coal gangue backfill (CCGB) is an engineering mixture that can effectively solve the surface subsidence problem, and comprises coal gangue and cementitious materials. However, there are many constraints regarding cost, performance, and other engineering indicators of CCGB. To optimize the performance, reduce the cost, and recycle agricultural solid waste, the replacement of fly ash in the raw material with the equal weight of corn straw fly ash (CSFA) was studied. The effects of adding CSFA on the uniaxial compressive strength (UCS), surface crack propagation, acoustic emission characteristics, shear strength, drying shrinkage, and microstructure of the CCGB were investigated experimentally by setting different substitution amounts (0, 10, 20, 30, and 40 wt%) and curing ages. The results show that CSFA can be used to replace up to 40 wt% of the fly ash in CCGB, and help improve the mechanical properties of CCGB, subject to the adverse effects of drying shrinkage. At higher substitution amounts, the UCS and shear strength were found to increase. Furthermore, the specimen exhibited a double-crack failure on the surface and X-shaped failure inside; otherwise, a single-crack failure on the surface and single-slope failure were observed. Compared to fly ash, CSFA has a coarser particle size, higher pozzolanic reactivity, more reactive silica/alumina, and later reaction stage as a supplementary cementitious material in CCGB. This introduction of CSFA into CCGB provides an excellent example of green and sustainable development.